Sobre a luz: discreta ou contínua? Uma atividade de física moderna no ensino médio - Almeida, Tiago Pereira (2024)
Modern physics is evident in tv shows, movies, news broadcasts, and various contemporary technologies. Nonetheless, research in physics education suggests that the school curriculum has not adapted to these advancements. Particularly concerning the topic of light, students typically only have contact with geometric optics, without exploring more current aspects of light. Given this scenario, this dissertation aims to evaluate the contributions of using experiments and computer animations to introduce and facilitate the learning of modern physics in high school. To achieve these objectives, a literature review was conducted on the use of experiments and computer animations to introduce concepts of physical optics. Subsequently, a teaching sequence was developed to address light concepts, using computer animations and experiments as didactic resources. Later, this sequence was applied in the classroom, and the contributions of the method used were evaluated, resulting in recommendations. To collect data, questionnaires, conceptual maps, and experimental activity scripts were used. The research adopted a qualitative approach and was based on the principles of meaningful learning for data analysis. This study contributes scientifically by addressing optics beyond the geometric perspective, through experiments and computer animations grounded in learning theories. The application of the teaching sequence resulted in greater motivation among students and good performance in experimental activities and scripts, indicating the construction of knowledge and evidence of meaningful learning by learners.